Multiple Omics Analyses Reveal Activation of Nitrogen Metabolism and Flavonoid Glycosylation in Toxicodendron vernicifluum Under High Temperature - Guoqing Bai; Ruiwen Ding; Qizhen Su; Xiaomin Ge; Shasha Li; Huiying Shang; Aiguo Zhao; Chen Chen (Biology)
Lacquer trees (Toxicodendron vernicifluum), economically vital, face high-temperature stress in summer. Transcriptomic, proteomic, and metabolomic analyses were employed to investigate the mechanisms by which lacquer trees respond to high temperatures. High-temperature treatment led to notable metabolite changes with 224 upregulated and 69 downregulated. Indole-3-acetic acid remained stable while abscisic acid decreased, with increases in jasmonic acid and jasmonoyl-L-isoleucine indicating complex hormonal responses. JAR1 and ABA 8′-hydroxylase encoding genes were upregulated. The rise in JAs boosted the alkaloid content and activated nitrogen transport. High temperatures also increased specific amino acids and upregulated aminotransferase and protease-encoding genes. Metabolomic analysis showed elevated flavonoid glycosides and the upregulation of glycosyltransferase genes. WPCNA found 35 protein modules involved in secondary metabolite biosynthesis, protein phosphorylation, and signal transduction. Protein–protein interaction analysis revealed MYC6’s link with flavonoid biosynthesis, indicating its role in promoting flavonoids.